The Relationship Between Childhood Trauma and Level of Resilience in Borderline Personality Disorder - Diana Atmaja; Titis Hadiati; Natalia Dewi Wardani (Diponegoro International Medical Journal, 2025)
Background: Borderline personality Disorder (BPD) is a serious mental disorder characterized by instability in emotions, impulse control, interpersonal relationships and self-image. Childhood trauma such as physical emotional or neglect abuse, has been strongly linked to the development of mental disorders, including BPD. Resilience as a psychological capacity to adapt to adversity, has also been shown to vary among individuals with BPD and may relate to their history of childhood trauma.Objective: To determine the relationship between childhood trauma and resilience level in BPDMethods: This study was a cross-sectional study, with 41 subjects were patients who had been diagnosed with BPD. Childhood trauma and resilience levels were assessed using the Childhood Trauma Questionnaire (CTQ) and Connor Davidson Resilience Scale (CD-RISC).Results: The relationship between emotional abuse and resilience level obtained a p = 0.008, physical abuse p = <0.001, sexual abuse p = 0.002 so that there is a significant relationship between emotional abuse, physical abuse and sexual abuse with resilience level in BPD.Conclusion:There was a significant relationship between childhood trauma emotional abuse, physical abuse and sexual abuse with the level of resilience in BPD patients.